ANALYSIS OF THE ECONOMIC POTENTIAL OF KARANGANYAR DISTRICT IN 2017-2022 - Elvira Ika Rosiana; Gentur Jalunggono; Emma Dwi Ratnasari (Transpublika Publisher, 2023)
The primary objective of economic development is to promote community prosperity. Assessing the progress of economic development relies on observing the region's economic growth, which is closely tied to the utilization of its existing economic potential. Maximizing the exploration and utilization of regional potential is crucial for fostering development. Identifying key sectors is instrumental in stimulating economic growth. The economic growth in Karanganyar Regency experienced fluctuations between 2017 and 2022. Thus, this study aims to identify the fundamental sectors in Karanganyar Regency, determine the potential and leading economic sectors to be developed, and contribute to economic growth in the region. Additionally, it analyzes the classification of regional economic sector growth in Karanganyar Regency from 2017 to 2022. The study employs secondary data, specifically time series data spanning from 2017 to 2022, obtained from the Central Statistics Agency (BPS) of Karanganyar Regency and Central Java Province. The data used encompass the Gross Regional Domestic Product (GRDP) by industry sectors based on the 2010 Standard Industrial Classification for Karanganyar Regency and Central Java Province. The research utilizes various methodologies, including Location Quotient (LQ) analysis, Growth Ratio Method (MRP), overlay analysis, and Klassen Typology. The findings of this study reveal that Karanganyar Regency, from 2017 to 2022, consists of (1) five fundamental economic sectors, (2) ten economically promising sectors with significant growth, (3) three potential economic sectors, and (4) three advanced and rapidly expanding sectors in Karanganyar Regency.